The ransomware dilemma : the decision on whether to pay up when cybercriminals hold data hostage is shaped by choices leaders made long before an attack - Leo, Philipp; Isik, Öykü; Muhly, Fabian (MIT Sloan Management Review, 2022)
Ransomware has become a global scourge, as gangs of cybercriminals use malware to encrypt victims' data and extort payment as a condition of restoring access. The majority of business leaders who fall prey to the tactic are unprepared for the scenario and wind up paying the ransom. The authors suggest a more considered approach to that decision and walk readers through six questions that can illuminate their options and inform their choices.